Intensified antibody response elicited by boost suggests immune memory in individuals administered two doses of SARS-CoV-2 inactivated vaccine - Yun Liao; Ying Zhang; Heng Zhao; Jing Pu; Zhimei Zhao; Dandan Li; Shengtao Fan; Li Yu; Xingli Xu; Lichun Wang; Guorun Jiang; Longding Liu; et al. (Emerging Microbes and Infections)
Neutralizing antibodies in the subjects of an inactivated SARS-CoV-2 vaccine clinical trial showed a decreasing trend over months. An investigation studying the third immunization suggested that the waning of neutralizing antibodies in individuals administered two doses of inactivated vaccine does not mean the disappearance of immunity.